5th International Scientific Conference on "Exercise and Quality of Life" - Cecil J. W. Meulenberg; Saša Pišot (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2019)
A delegation of the Institute for Kinesiology Research attended the hospitable EQOL2019 in Novi Sad, organised by the Faculty of Sports and Physical Education of the University of Novi Sad. The plenary lectures of the conference in a very informative way, covered various aspects within the subtopic 'from active childhood to healthy aging'.